Key role of activated platelets in the enhanced adhesion of circulating leucocyte-platelet aggregates to the dysfunctional endothelium in early-stage COPD - Marques, Patrice; Bocigas, Irene; Domingo, Elena; Francisco, Vera; Tarraso, Julia; Garcia-Sanjuan, Yolanda; Morcillo, Esteban J.; Piqueras, Laura; Signes-Costa, Jaime; González, Cruz; Sanz, Maria-Jesus (Frontiers in Immunology, 2024)
Background: Chronic obstructive pulmonary disease (COPD), usually caused by long-term tobacco smoking, is independently associated with systemic inflammation. However, little is known about the systemic inflammatory status of patients with early-stage COPD (classified as GOLD 1) and long-term smokers with normal lung function (LF). Here, we characterised the early changes in the associated inflammatory state in patients with GOLD 1 and in long-term smokers with normal LF. Methods: Fresh blood samples from 27 patients with GOLD 1, 27 long-term smokers and 14 non-smokers were analysed. Results: Ex vivo blood analysis revealed greater leucocyte-platelet adhesion to TNFα-stimulated pulmonary endothelium in patients with GOLD 1 than in smokers and non-smokers. In addition, platelet reactivity (platelet count and activation, and fibrinogen levels) and the frequency of leucocyte-platelet aggregates were higher in the GOLD 1 group than in the other groups. Some of these findings correlated with the severity of lung dysfunction, while platelet hyperactivity correlated positively with leucocyte-platelet adhesion. The GOLD 1 group also had a higher Th17/Treg ratio and higher circulating levels of IL-17C and C-reactive protein than the other groups. However, long-term smokers also had higher leucocyte counts and activation, and higher plasma levels of TNFα and IL-6 than non-smokers. Conclusions: Our data suggest that the altered inflammatory parameters in long-term smokers may represent early biomarkers of COPD. Accordingly, peripheral immune monitoring based on the above parameters may be useful to prevent disease progression in long-term smokers with normal LF and early COPD.